Subjection of the Constitutional Tribunal to the organs of political authorities in Poland after 2015: contribution to considerations (Ius Novum, 2022)
The article discusses the issues concerning the influence of the Polish legislative poweron the functioning of the Constitutional Tribunal that started in the autumn of 2015. Theanalysis covers all legal acts passed between 2015 and 2017 that introduced changes in thestructure and functioning of the Constitutional Tribunal and modified the status of its judges.The research made use of the innovative method devised by Professor Paweł Chmielnicki,which consists in the examination of substantial sources of law, i.e. real reasons for passinga given statute. The analysis covers, inter alia, materials developed by a group of specialists,including the author, employed by the Centre for Legislative Process Research at LazarskiUniversity. The article shows that the changes in the Constitutional Tribunal do not serveto exercise citizens’ rights. They aim to strengthen the political authorities (the Parliamentand its emanation, the Government) at the judicial power expense. It matches the generaltendency visible after the 2015 parliamentary election targeted at weakening the position of the judiciary and personal influence of the legislative on this power. The activities do not follow the constitutional rule of separation of powers and are in conflict with the principle ofseparation and independence of courts and tribunals guaranteed by the Constitution. Takinginto account the fact that authorities change in the conditions of a democratic system, theonly panacea for the restoration of the shape and prestige of the Constitutional Tribunal isthe change of the authorities. There will be an opportunity for that in the autumn of 2023.
Keywords: tripartite system of the separation of powers; the judicial; Constitutional Tribunal; independence; strengthening authorities; protection of the weaker